Millennial Jihad in the Digital Age: Critical Discourse Analysis of Self-Radicalization and Self-Recruitment among the Millenial Generation - Suryanatha, Ida Bagus; Selvia, Fitriana; Ayu, Katriana Puspita (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This investigation delves into the profound impact of technology and social media by examining jihad narratives within the millennial demographic. The millennial generation, employing an innovative strategy of self-directed learning, has moulded propositions, paradigms, dual meanings, and religious narratives, resulting in the emergence of two pivotal terms: self-radicalization and self-recruits. Utilising Teun A Van Dijk’s critical discourse analysis, we scrutinise a news item, unraveling discourses and multiple meanings. Our findings intricately expound upon the contextualisation of millennials, technology, the Internet, social media, YouTube, radicalism, jihad, and religious narratives—a trilogy that introduces a groundbreaking terminology: Critical discourse analysis of self-religious narratives, with a specific focus on self-radicalization and self-recruitment. This study propels our comprehension of how millennials navigate and influence religious discourses in the era of digital communication.